GGR Biennial Critical Review: Analytical Developments Since 2014 - Linge, Kathryn; Bédard, L.; Bugoi, R.; Enzweiler, J.; Jochum, K.; Kilian, R.; Liu, J.; Marin-Carbonne, J.; Merchel, S.; Munnik, F.; Morales, L.; Rollion-Bard, C.; et al. (Wiley-Blackwell Publishing, 2017)
© 2017 The Authors. Geostandards and Geoanalytical Research © 2017 International Association of Geoanalysts This GGR biennial critical review covers developments and innovations in key analytical methods published since January 2014, relevant to the chemical, isotopic and crystallographic characterisation of geological and environmental materials. In nine selected analytical fields, publications considered to be of wide significance are summarised, background information is provided and their importance evaluated. In addition to instrumental technologies, this review also presents a summary of new developments in the preparation and characterisation of rock, microanalytical and isotopic reference materials, including a précis of recent changes and revisions to ISO guidelines for reference material characterisation and reporting. Selected reports are provided of isotope ratio determinations by both solution nebulisation MC-ICP-MS and laser ablation-ICP-MS, as well as of radioactive isotope geochronology by LA-ICP-MS. Most of the analytical techniques elaborated continue to provide new applications for geochemical analysis; however, it is noted that instrumental neutron activation analysis has become less popular in recent years, mostly due to the reduced availability of nuclear reactors to act as a neutron source. Many of the newer applications reported here provide analysis at increasingly finer resolution. Examples include atom probe tomography, a very sensitive method providing atomic scale information, nanoscale SIMS, for isotopic imaging of geological and biological samples, and micro-XRF, which has a spatial resolution many orders of magnitude smaller than conventional XRF.